What a Wonderful World: The Metaphysical Monism of Plato under the Two-Level Model of Holger Thesleff - Alican, Necip Fikri (Cosmos and History: The Journal of Natural and Social Philosophy, 2024)
This paper is an appraisal of the two-level model of Holger Thesleff for the interpretation of Plato. The primary emphasis is on the metaphysics of the model, which revolves around the idea of a single world composed of two levels complementing each other in a productive relationship. The ultimate goal is to show that the monism of two levels in one world is a better alternative than the metaphysical dualism traditionally attributed to Plato to account for the transcendence typically associated with his Forms, which ipso facto become separated from the very reality they are supposed to fashion and regulate. While the segregation alone might automatically count against the postulation of a separate world for the Forms, the trick in promoting a solitary world instead is to retain some semblance of transcendence, or an acceptable alternative to it, while compressing everything into the same reality. The present initiative shows that it is not a trick of any sort, certainly not in the sense of a ruse, but a philosophical vision originating with Plato himself.